Cultura come cibo - Amidei, Beatrice Barbiellini; Marazzi, Martino (Ledizioni - LediPublishing, 2017)
The theme of the contributions is the centrality of culture, referring to the Dante metaphor of the sapiential banquet and of "culture as food." The interventions intend to stimulate the start of an interdisciplinary reflection on the humanities in their sense of complex field and creative practice. Starting from different disciplines - from philosophy to literature and anthropology - and through dialogue between literati of various backgrounds, a perspective is proposed that encourages the encounter between "high" and "low" and between elite culture and folkloric culture . The arc of interest ranges from the texts of ancient Indian literature, to the Grail of Chrétien de Troyes and to the philosophical formation offered to the public by Dante's Convivio; from the fascinating stratification of traditional knowledge in the Lunari, to the carnival folkloric practices and to the imagination of the Land of Cockaigne; and again from the use of food as belonging in the writings of Italian emigrants in America.